Safety Standards in Management and Engineering Policies at the Sidoarjo Transportation Agency: Standart Keselamatan dalam kebijakan Manajemen dan Rekayasa di Dishub Sidoarjo - Anjarsari, Surya; Hariyanto, Didik (Indonesian Journal of Public Policy Review, 2020)
This study aims to describe and analyze the implementation of management policies and control controls in reducing traffic accidents in the Tulangan area of ​​Sidoarjo Regency. Data collection techniques through observation, interviews and documentation. In the data analysis technique using data reduction, data presentation and conclusions. The results of this study indicate that the safety standard in traffic management and engineering policies, namely the Bureaucratic Structure in organizational planning, has been well controlled. Resources in preparing policy formulation materials are divided into two parts, namely the Management Section and the Traffic Engineering Section with several personnel who have the competence to implement a policy plan for regulating the use of road networks and traffic movements. Disposition in the policy forms the attitude of the implementer, namely providing program support and commitment in carrying out traffic management and engineering policies. Communication is carried out by coordinating between implementers in traffic safety standards by carrying out safety for schools and the community. . So that there are several influencing factors in traffic management and engineering policies, such as several complaints from the public because the service has not been fully satisfactory, so a survey is needed by looking at traffic conditions and the need for improvement.